Effect of Dolomite as Expansive Agent and Shrinkage Reducing Admixture in Self-Compacting Shrinkage – Compensating Concrete (Journal of University of Babylon for Engineering Sciences, 2018)
The principle of using expansive agents has been recommended to manufacture shrinkage compensating concrete provided that an adequate wet curing is carried out. On the other hand, shrinkage-reducing admixture (SRA) in the concrete mixes, has been more recently suggested to reduce the risk of cracking in concrete structures caused by drying shrinkage.This paper is devoted to the study of the influence of complex modifier in the form of superplasticizer, shrinkage reducing admixture and expansive agent CaO- MgO-based on the fresh properties, hardening processand restrained shrinkage of Self-Compacting-Shrinkage-Compensating Concretes. The combined addition of shrinkage-reducing admixture with expansive agent has been found to be successful in producing shrinkage-compensating concrete. It should be noted also that the shrinkage reducing admixture slightly improve the workabilityof the fresh concrete mixtures but, it slightly reduces the early compressive strength of concrete.